Bilateral talon cusps $rowena V. Maunahan. - Maunahan, Rowena V. (The Journal of the Philippine Dental Association)
Clinical problems that may arise because of the talon cusps include stagnation of food debris, caries-susceptible developmental grooves, soft tissue irritation, esthetics, occlusal interference, periapical lesions and problems in diagnosis and clinical management for dentists.